Anthropometric Measurements and Inflammatory Marker in Obese Women - Kartika Rizky Aulia; Meita Hendrianingtyas; Edward Kurnia Setiawan Limijadi; Dodik Pramono (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2022)
Background: Obesity is one of global epidemic health problems and its prevalence is higher among women. Obesity can cause low grade chronic inflammation mechanism in adipose tissue, which is characterized by the increase of proinflammatory cytokines and adipokines. Neutrophil lymphocyte ratio (NLR) is a simple inflammatory marker which can be reliable in evaluating the inflammatory status occurring in obese women. Waist to height ratio (WHtR) and waist to hip ratio (WHR) are anthropometric measurements, have been reported to be associated with obesity and risk of metabolic syndrome.Objective: This study aimed to determine the correlation of WHtR and WHR with NLR in population of obese women.Materials and Methods: This was a cross sectional study enrolling 80 obese women with Body mass index (BMI) > 27 aged 30 - 50 years in National Diponegoro Hospital Semarang, Indonesia. WHtR was determined by dividing waist circumference by height and WHR was determined by dividing waist circumference by hip circumference. NLR was examined manually from automatic hematology analyzer by dividing absolute neutrophil count (ANC) and absolute lymphocyte count (ALC). Spearman correlation test was performed, p<0.05 was considered as statistically significant.Results: There was significant weak positive correlation between WHtR and NLR in obese women (p = 0,046; r = 0,224). There was no significant correlation between WHR and NLR in obese women (p = 0,961; r = 0,006).Conclusion: The present study showed that WHtR is one of better anthropometric measurement because it is associate with NLR as a simple marker of inflammation in obese women.